1997
DOI: 10.1116/1.580438
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and phase of tin oxide thin films during their growth from the metallic tin

Abstract: Thin tin films were deposited on oxidized silicon substrates by sputtering. Changes in both the phase and morphology of the films were studied as a function of the annealing process, time and atmosphere. X-ray diffraction (XRD) analysis was used to study phase evolution of the films during annealing. Atomic force microscopy and scanning electron microscopy were employed to characterize microstructure and morphology of the films. XRD analyses revealed phase transformations from metallic Sn to romarchite and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We refer the reader to their paper for additional data. Chung et al (1997) detected romarchite using X-ray diffraction in an investigation of a film of pure tin in air and oxygen. They reported that SnO was the initial tin phase to form by oxidation, but that it subsequently transformed into SnO 2 .…”
Section: Background Informationmentioning
confidence: 99%
“…We refer the reader to their paper for additional data. Chung et al (1997) detected romarchite using X-ray diffraction in an investigation of a film of pure tin in air and oxygen. They reported that SnO was the initial tin phase to form by oxidation, but that it subsequently transformed into SnO 2 .…”
Section: Background Informationmentioning
confidence: 99%
“…These include ultrahigh vacuum and reactive electron beam evaporation [3][4][5][6][7][8][9][10], chemical vapor deposition (CVD) by thermal, plasma or laser technique [11][12][13], reactive radio-frequency (RF) or magnetron sputtering [14][15][16][17][18][19][20][21][22][23][24][25][26], laser ablation [27][28][29][30][31][32], the sol-gel technique [32][33][34][35][36], screen printing technology [37,38], electrochemical deposition [7,39], and pyrosol methods [40][41][42][43]. Various techniques have been used for the deposition of the gas-sensitive layer.…”
Section: Introductionmentioning
confidence: 99%
“…10 The growth of sputtered films has been studied by atomic force microscopy. 11,12 However, to our knowledge this is the first attempt to characterize sputtered SnO 2 growth by elastic light scattering.…”
Section: Introductionmentioning
confidence: 99%